O regime fabril-artesanal de violas paulistas - Brito, Rainer Miranda (Universidade Federal de São Carlos, 2015)
How a brazilian viola come to its existence inside an artisan and manufacture environment? The materials allocated in such environment of craft arrange under specific conditions variable routes for one task: the precise and risky establishment of material compatibility degrees in each technical circumstance. When contouring the artisan and manufacture environment the object viola refracts the discourses about its existence in favor of the resources which assure its well defined boundaries. Whatever the discourses about the web-frames of that craft surrounding, it is through its functional inboard where the technical activity exposes its irreducibles: the technically articulated resources. A craft environment from Sao Paulo’s countryside thus assign to this research a problem of Comparative Technology, limiting this research to a focal descriptive procedure as a methodological experiment guided by rhytms of construction and repair of brazilian violas inside the craft environment – as far stand its instruments, tools, machinery and products. The frame of this Comparative Technology study is the processes of internal compatibility of a craft environment: the object viola is a process, a topical serie able to reconfiguration.
Keywords: Tecnologia comparada; Viola; Metodologia; Antropologia da técnica; Comparative technology; Brazilian viola; Methodology; Anthropology of technics; CIENCIAS HUMANAS::ANTROPOLOGIA